Drawing Creator of Worlds. Criticism and Representation of the City in Comics (diségno, 2021)
In the Walking city illustrations, large insect-cities walk the earth, while the materialization of what will be the interconnection concept is the protagonist of the project for the Plug-in-city. This was a vision where megastructures populate the world, while single housing units, transfigured into space capsules, hook and unhook there. In these utopian visions, Archigram blend graphic codes of Marvel covers, Pop Art references and the language of science fiction comics. The graphical medium, thanks to the immediacy of the sign and the vividness of the colors, is the ideal tool to give back a radical image, which is able to bring out bolder concepts than the traditional ones. The fusion between architecture and comics thus becomes instrumental in the creation of a futuristic vision, whichstarts from the analysis of a nearby reality. The world of comics also deals by nature with the drawing of an environment aimed at portraying real or ideal cities or real caprices, where architectures distant in time and space are mixed, sometimes with fantasy elements or projects never realized, to form new plausible imagery. Today more than ever, the comic strip is not limited to passively reflect the society, but it offers a criticism and it opens reflections also on architectural and urban issues. Through the analysis of the drawings of some exemplary comics, the research proposes to highlight the creation of visionary worlds capable of focusing on specific architectures and on the contemporary city.
Keywords: comics; visionary architecture; criticism; drawing; representation